Análise da influência do mandrilamento na integridade superficial do aço inoxidável super duplex - Morelo, Fernando (2014)
Super duplex stainless steel is a material widely used in oil and gas industry and boring is one of the manufacturing processes used to manufacture components for this industry. The finishing surface generated by boring process is very important once these parts are exposed to great corrosive attacks by being in contact with oil and gas acids and, also, because they are used at big depths and high pressures in the seabed. The need of using dampened boring bars occurs when the length is four times greater than the machined diameter. It was used one of these dampened boring bars to analyze its influence on a boring processes, with its length eight times its diameter. The material used for this study is the super duplex stainless steel SAF2507. Input variables for analysis were cutting speed, feed, nose radius of the cutting tool and coolant pressure. For analysis of the material integrity it was measured the surface roughness using Sq, Ssk, Sku, Str, Sal, Sk, Sk, SvK parameters, residual stress, hardness and machining temperature dissipated in part region. The results have shown the presence of residual tensile stress with increasing hardness when Sk roughness is up to 2 μm and Sk roughness below 2 μm showed low residual tensile or residual tensile compression. The average temperature dissipated in the proof body was 33.6 °C, and the temperature in the region play-chip-tool was 350 oC. The best combination of cutting conditions found for the lowest roughness values and residual compressive stress were, finishing, cutting depth of 0.4 mm was the highest cutting speed (140 m / min), the lowest forward (0.1 mm / rev), smaller radius (0.4 mm) and the lower pressure coolant (15bar).